Peranan KH. Ahmad Taufiq Hasnuri Dalam Dakwah Islam di Kota Palembang Provinsi Sumatera Selatan (1420-1441 H / 2000-2019 M) - Farhan Pranata; Endang Rochmiatun; Padila Padila (Program Studi Sejarah Peradaban Islam UIN Raden Fatah Palembang, 2022)
This writing is entitled The Role of KH. Ahmad Taufiq Hasnuri in Syiar Islam in Palembang City, South Sumatra Province (1420-1441 H/2000-2019 AD). In this paper discusses the history of KH. Ahmad Taufiq Hasnuri on social life and education. And the role of KH. Ahmad Taufiq Hasnuri in the development of Islamic symbols in the city of Palembang. In this paper, historical methods are used with stages, heuristics, source criticism, interpretation, and historiography. The theory used in this research is the role theory proposed by Soejono Soekanto. KH Ahmad Taufiq Hasnuri is a phenomenal local cleric with the characteristics of his da'wah so that it is accepted and developed in the community.